Rise of the snakes - West, Tracey, 1965- (Scholastic, 2012)
"Ever since Lord Garmadon retreated to the underworld, peace has spread throughout the land of Ninjago. But now there is a new threat -- Lloyd Garmadon, Lord Garmadon's son! At first, Cole, Jay, Kai, and Zane don't take Lloyd seriously. After all his main goal is stealing candy from villagers. But all that changes when Lloyd accidentally awakens the Serpentine, a race of powerful snake-headed beasts who've been banished for centuries. Can the four ninja ride to the rescue before the sinister Serpentine hypnotize all the citizens of Ninjago?"--Back cover.